WAYS TO REDUCE THE SEVERITY OF BENDOPNEA AS A PROGNOSTIC SIGN OF DECOMPENSATION OF CHRONIC HEART FAILURE - Abdullayeva K. H.; Uzbekova N. R.; Bektasheva G. M. (European Science Publishing, 2024)
We have frequently found that patients with heart disappointment had shortness of breath when bowing forward. The frequency of bendopnea in patients with decompensated heart disappointment (DHF), its repercussions on quality of life (QoL), and its prognosis have not however been considered. This think about was carried out to assess the characteristics, degree of limitation, and short-term guess of patients with bendopnea and DHF.
Keywords: Bendopne, decompensated heart disappointment, quality of life, mortality.